Discrete mathematical structures : a succinct foundation - Kumar, B. V. Senthil; Dutta, Hemen, 1981- (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2020)
"This book contains fundamental concepts on discrete mathematical structures in a crispy style so that learners could grasp the contents and explanation easily. The concepts of discrete mathematical structures have lot of applications in computer science, engineering and information technology including in coding techniques, switching circuits, pointers and linked allocation, error corrections, as well as in data networking, Chemistry, Biology and many other significant scientific areas. The book is for undergraduate and graduate levels learners and educators associated with various courses and progammes in Mathematics, Computer Science, Engineering and Information Technology. The book should serve as a text and reference guide to many undergraduate and graduate programmes of the disciplines mentioned above being offered by many institutions including colleges and universities. Readers will find solved examples and end of the chapter exercise in each chapter for practise and enhance the understanding of topics discussed"--
OCLC-licensed vendor bibliographic record.
Keywords: Computer science -- Mathematics; COMPUTERS / Operating Systems / General; MATHEMATICS / Combinatorics; TECHNOLOGY / Electricity